Factor influencing public participation in urban agriculture in Malaysia - Rezai, Golnaz; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin; Sharifuddin, Juwaidah (2014)
As population grows, the need to provide more jobs and food are becoming more complex both economically and physically. Urban agriculture has drawn much attention in Malaysia to tackle problems caused by population growth, urbanization and food scarcity. This interest in urban agriculture in the country has set the scene to explore factors influencing public involvement in it. To gather information for this study a total of 640 households were interviewed via a structured questionnaire. Exploratory factor analysis was carried out and the results show that society recognition, attitude and the social impact of urban agriculture are the top three considerations for individuals participating in urban agricultural activities.